I knew you could! : a book for all the stops in your life - Dorfman, Craig; Ong, Cristina (New York : Platt & Munk, 2003)
"The Little Engine that Could" advises how to find one's own track, handle life's ups and downs, and even face the dark tunnels that can make one frightened or sad.
3.1
K-3
K-3.
Publisher's Weekly
NP
Keywords: Railroads -- Trains -- Fiction; Self-reliance -- Fiction; Stories in rhyme; Railroads -- Fiction; Self-reliance -- Fiction; Stories in rhyme